Glocalized Experiential Learning Infused Resource Package in Earth and Life Science - Nagal, Raphael Kevin (JPAIR Multidisciplinary Research, 2020)
The study aimed towards the development and evaluation of glocalized experiential learning-infused resource package in Earth and Life Science. The study used the educational design research method and involved the generation of a learning resource package. Participants of the study include the Grade 11 students of LNFVHS, S.Y. 2019-2020, as well as learning experts. Both qualitative and quantitative data were gathered for the study. Qualitative data came from focus group discussions, while quantitative data came from the results of the Bioenergetics test and Learning Material Evaluation Form. The least mastered competencies generated were The Cell, Photosynthetic Reactions, and Acquisition and Utilization of Energy. From this result, a glocalized experiential learning infused resource package was developed consisting of three learning materials based on the least mastered concepts–two (2) print materials (Learner’s Material and Teacher’s Guide) and one (1) non-print (Video-Based Module). The resource package was rated as very acceptable (3.70 for Learner’s Material, 3.65 for Teacher’s Guide, and 3.62 for the Video-Based Module). The study revealed that when learning materials were glocalized, contextualized, and infused with experiential learning activities, learners were more likely to be engaged in learning the concepts. The learning package developed helped in encouraging independent learning and a good source of supplemental learning material for Grade 11 and other grade levels.